RANCANG BANGUN PENGAMAN MATA DENGAN LAYAR TV BERBASIS ARDUINO UNO - Andy Nugroho Prio Utomo; Edy Kurniawan; Muh Muhsin (Universitas Muhammadiyah Ponorogo, 2021)
Television is an electronic device which now the majority is owned by all Indonesians. Besides the use of this electronic device, there is a negative impact or thing that is contained in this electronic device. When watching television, eyes often experience tired and dry eyes, this is caused by television monitors that emit radiation rays and cause several eye problems. The radiation beam emitted from each television differs depending on the size of the monitor. This has been proven by tests that have been carried out by related institutions that the distance to watch television for each monitor is different.